Internet: the reality of use and the prevention of effects - El Fadl, Mohamed Ibrahim Mohamed (Arab Journal for Sciences and Research Publishing, 2016)
The paper attempted to to examine the reality of the use of the Internet and identify the negative effects for students of Bahri University and the ways of preventing the disadvantages of effects. , To achieve the purposes of the paper the researcher prepared a scale to determine the degree of use and another to find out the negative effects of the use for the sample (150) of students. The Social Survey Methodology was used to assess the data in which the revealed spss procedures were employed to acount the frequencies, averages and percentages of the obtained data. , and finding revealed many result, the most important of Which Were proving the Internet addiction for the sample, in addition, the realization of the negative effects which were highly academic and health aspects, from the students themselves point of view. And then the researcher presented the most important recommendations in the following: The need for attention sensitizing programs for students about the phenomenon of addiction use of the Internet to reduce the negative effects caused by them. The need for interaction with educational institutions, departments and units of the academic and health guidance for the development of academic and health aspects of the students.
Keywords: Internet addiction; prevention; impact